A Preexistent Hypoxic Gene Signature Predicts Impaired Islet Graft Function and Glucose Homeostasis. Issue 11 (November 2013) - Cantley, James; Walters, Stacey N.; Jung, Min-Ho; Weinberg, Anita; Cowley, Mark J.; Whitworth, P. Tess; Kaplan, Warren; Hawthorne, Wayne J.; O'connell, Philip J.; Weir, Gordon; Grey, Shane T.
We examined whether hypoxic exposure prior to the event of transplantation would have a positive or negative effect upon later islet graft function. Mouse islets exposed to hypoxic culture were transplanted into syngeneic recipients. Islet graft function, β-cell physiology, as well as molecular changes were examined. Expression of hypoxia-response genes in human islets pre- and posttransplant was examined by microarray. Hypoxia-preexposed murine islet grafts provided poor glycemic control in their syngeneic recipients, marked by persistent hyperglycemia and pronounced glucose intolerance with failed first- and second-phase glucose-stimulated insulin secretion in vivo. Mechanistically, hypoxic preexposure stabilized HIF-1α with a concomitant increase in hypoxic-response genes including LDHA, and a molecular gene set, which would favor glycolysis and lactate production and impair glucose sensing. Indeed, static incubation studies showed that hypoxia-exposed islets exhibited dysregulated glucose responsiveness with elevated basal insulin secretion. Isolated human islets, prior to transplantation, express a characteristic hypoxia-response gene expression signature, including high levels of LDHA, which is maintained posttransplant. Hypoxic preexposure of an islet graft drives a HIF-dependent switch to glycolysis with subsequent poor glycemic control and loss of glucose-stimulated insulin secretion (GSIS). Early intervention to reverse or prevent these hypoxia-induced metabolic gene changes may improve clinical islet transplantation.